Accounting For Expenses in Grain Processing Clusters. - Abdilalimov Akmaljon Obidzhanovich (Genius Publishing Group, 2021)
The article describes the disappearance of the cost of grain and the analysis of cost accounting in grain processing clusters and the features of cost accounting
Keywords: Production; cost price; pairing of accounts; debit and credit